Digital wildlife photography - Gerlach, John. (Focal Press, 2013)
"From how many frames you need to shoot per second to capture that WOW moment to where to focus on a bird with a big beak to get the best depth of field, this book has it all for the wildlife photographer. It is an impressive mix of technology with just plain good advice for image-taking, and they discuss each point specifically for shooting wildlife, because it is a totally unique type of photography. The lighting and shutter speed for a macro flower shot is not the same that you'd need for a bird in flight or a kangaroo jumping across a field. Mix together this fantastic info with the many years of experience that the Gerlachs have shooting and teaching and the absolutely jaw-dropping images and you really do have a perfect storm for a book"--